2017
DOI: 10.1093/gbe/evw283
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of fluid sets of hairpin-derived 21-/24-nt-long small RNAs at seed set uncovers special epigenetic features in Picea glauca

Abstract: Conifers’ exceptionally large genome (20–30 Gb) is scattered with 60% retrotransposon (RT) components and we have little knowledge on their origin and evolutionary implications. RTs may impede the expression of flanking genes and provide sources of the formation of novel small RNA (sRNAs) populations to constrain events of transposon (TE) proliferation/transposition. Here we show a declining expression of 24-nt-long sRNAs and low expression levels of their key processing gene, pgRTL2 (RNASE THREE LIKE 2) at se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 85 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…The other aspect aims to investigate whether MIRNA s originate from TEs and undergo evolution coupled in time with genome evolution between species within spermatophyte and how the environment contributes to adaptive variation at molecular levels (e.g., epigenetic imprinting, genetic variants, etc.). This conception is emanated from our results concerning MIRNA s for abundant sRNAs in Arabidopsis (i.e., conserved miRNAs) containing more DNA repeat modules than those for enriched ones in P. glauca (Figure S8 ; also see Liu and El-Kassaby, 2017b ). This may be linked to their giga-genome evolution, in the sense that genetic divergence is suppressed in conifers, thus leading to few WGDs.…”
Section: Conclusion and Prospectsmentioning
confidence: 72%
“…The other aspect aims to investigate whether MIRNA s originate from TEs and undergo evolution coupled in time with genome evolution between species within spermatophyte and how the environment contributes to adaptive variation at molecular levels (e.g., epigenetic imprinting, genetic variants, etc.). This conception is emanated from our results concerning MIRNA s for abundant sRNAs in Arabidopsis (i.e., conserved miRNAs) containing more DNA repeat modules than those for enriched ones in P. glauca (Figure S8 ; also see Liu and El-Kassaby, 2017b ). This may be linked to their giga-genome evolution, in the sense that genetic divergence is suppressed in conifers, thus leading to few WGDs.…”
Section: Conclusion and Prospectsmentioning
confidence: 72%
“…3c,d ). The 20–22 nts plant sRNA mediate target gene cleavage or inhibition of protein translation, while the 24 nt sRNA class affects chromatin modelling of target genes 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Since all land plants and green algae possess the small RNA-generating RNAi machinery ( You et al, 2017 ), it is conceivable that gymnosperms, ferns and club mosses can potentially accumulate siRNAs derived from endogenous caulimovirids and/or their extant not-yet-identified episomal counterparts. Likewise, genomes of all land plants contain long terminal repeat (LTR) retrotransposons of the families Metaviridae (Ty3/Gypsy) and Pseudoviridae (Ty1/Copia) which can give rise to siRNAs as has been reported for the angiosperms A. thaliana ( Creasey et al, 2014 ; Masuta et al, 2017 ), strawberry ( Šurbanovski et al, 2016 ), mangrove ( Wang Y. et al, 2018 ), maize ( Alejandri-Ramírez et al, 2018 ) and wheat ( Sun et al, 2013 ); transposon-derived small RNAs were also reported for gymnosperms such as Picea glauca ( Liu and El-Kassaby, 2017 ) and Cryptomeria japonica ( Ujino-Ihara et al, 2018 ).…”
Section: All Families Of Land Plant Viruses and Viroids Spawn Small Rmentioning
confidence: 90%